2010
DOI: 10.1097/hjh.0b013e328339f9fa
|View full text |Cite
|
Sign up to set email alerts
|

Reduced discontinuation of antihypertensive treatment by two-drug combination as first step. Evidence from daily life practice

Abstract: Initiating treatment with a combination of two drugs is associated with a reduced risk of treatment discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 31 publications
7
75
0
14
Order By: Relevance
“…24 Our study is not completely devoid of inaccuracies because of use of only nonfatal CV events, misclassification of patients by errors in coding, and prescriptions of BP-lowering drugs for conditions other than hypertension. However, none of these limitations appears to endanger the interpretation of our findings, because antihypertensive drug trials have shown that the benefit of antihypertensive treatment is directionally similar for nonfatal and fatal CV events, 15 Lombardy hospital discharge and drug prescription databases show a close concordance either with population-based local registry of coronary and cerebrovascular events 25 and with data provided by a network of Italian general practitioners, 10 and, in Italy, hypertension represents by far the most common reason for prescribing BP-lowering drugs. 26 Finally, because in our study allocation of antihypertensive therapy was not randomized, the results may be affected by confounding factors.…”
Section: Corrao Et Al Combination Therapy In Hypertension 569mentioning
confidence: 73%
See 1 more Smart Citation
“…24 Our study is not completely devoid of inaccuracies because of use of only nonfatal CV events, misclassification of patients by errors in coding, and prescriptions of BP-lowering drugs for conditions other than hypertension. However, none of these limitations appears to endanger the interpretation of our findings, because antihypertensive drug trials have shown that the benefit of antihypertensive treatment is directionally similar for nonfatal and fatal CV events, 15 Lombardy hospital discharge and drug prescription databases show a close concordance either with population-based local registry of coronary and cerebrovascular events 25 and with data provided by a network of Italian general practitioners, 10 and, in Italy, hypertension represents by far the most common reason for prescribing BP-lowering drugs. 26 Finally, because in our study allocation of antihypertensive therapy was not randomized, the results may be affected by confounding factors.…”
Section: Corrao Et Al Combination Therapy In Hypertension 569mentioning
confidence: 73%
“…The clinical characteristics of patients undergoing different treatment regimens were obtained from the Health Search/Cambridge Structural Database (HSD), which provided patient records from Ͼ700 general practitioners, as reported in detail previously. 10 The cohort of HSD patients who started BP-lowering drug therapy from 2004 until 2007 was identified and selected as was done for the Lombardy cohort. In addition, patients were classified according to 3 pieces of clinical information that were not available from the Lombardy database, that is, severity of hypertension (mild, moderate, or severe), chronic disease score (0, 1, or 2 according to the coexistence of comorbidities, such as heart failure, peripheral artery disease, diabetes mellitus, dyslipidemia, and chronic kidney disease), and body mass index (Ͻ25, 25 to 30, or Ͼ30 kg/m 2 ).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…10,32 It was also found to be majorly affected by patients' demography, cotreatments, type and severity of diseases of cardiovascular or noncardiovascular nature, and even adversely influenced by unexpected variables, such as residence in metropolitan areas and density of the population where the patient lived. 33 It should be emphasized that knowledge of the factors involved in low adherence to treatment is preliminary to and fundamental for any action that aims at reducing the extent of this phenomenon in real life. For hypertension, dyslipidemia, and diabetes mellitus, this would be the most crucial means to improve cardiovascular prevention strategies because for all these diseases nonadherence is majorly responsible for the strikingly low rate of their therapeutic control.…”
Section: Profiles Of Drug Usementioning
confidence: 99%
“…Zalety rozpoczynania leczenia hipotensyjnego od razu od terapii skojarzonej obejmują szybszą odpowiedź na leczenie u większej liczby pacjentów (co jest potencjalnie korzystne u osób z grupy dużego ryzyka), większe prawdopodobieństwo uzyskania docelowego BP u chorego z początkowo wyższymi wartościami BP, a także mniejsze prawdopodobieństwo zniechęcenia pacjenta w związku z wieloma zmianami terapii. W istocie w niedawnym badaniu przekrojowym wykazano, że pacjenci poddani leczeniu skojarzonemu rzadziej przerywają terapię niż ci, u których stosuje się dowolną monoterapię [447]. Dodatkową zaletą jest fizjologiczna i farmakologiczna synergia różnych klas leków, która nie tylko może prowadzić do większego obniżenia BP, ale również być przyczyną rzadszego występowania objawów ubocznych i przynosić większe korzyści niż te, które daje 1 lek.…”
Section: Zalety I Wady Obu Sposobów Postępowaniaunclassified